2019
DOI: 10.1016/j.exger.2018.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of all-extremity high-intensity interval training vs. moderate-intensity continuous training on aerobic fitness in middle-aged and older adults with type 2 diabetes: A randomized controlled trial

Abstract: Aging and diabetes are associated with decreased aerobic fitness, an independent predictor of mortality. Aerobic exercise is prescribed to improve aerobic fitness; however, middle-aged/older diabetic patients often suffer from mobility limitations which restrict walking. Non-weightbearing/low-impact exercise is recommended but the optimal exercise prescription is uncertain. The goal of this randomized controlled trial was twofold: 1) to test if high-intensity interval training (HIIT) and moderate-intensity con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
1
10

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 32 publications
1
43
1
10
Order By: Relevance
“…Dropouts: After randomization, two participants could not complete the protocol due to orthopedic complaints. [30,49,60,62,67,70,71,81,84,85]. However, some studies found HIIT to be superior [21,28,59,61,82].…”
Section: Hiit and Aerobic Fitnessmentioning
confidence: 99%
“…Dropouts: After randomization, two participants could not complete the protocol due to orthopedic complaints. [30,49,60,62,67,70,71,81,84,85]. However, some studies found HIIT to be superior [21,28,59,61,82].…”
Section: Hiit and Aerobic Fitnessmentioning
confidence: 99%
“…HIIT can be considered as a suitable supplement of strength training method in the elderly, and studies have shown that HIIT can improve the physical performance of the elderly group (68)(69)(70). In particular, when referring to the specific practicing strategy, the elderly are recommended to perform HIIT step by step.…”
Section: Discussionmentioning
confidence: 99%
“…Penelitian dengan observasi selama 1 tahun terhadap penderita diabet tipe 2, ternyata latihan dengan intetensitas tinggi adalah hanya yang paling berpengaruh untuk memperbaiki komplikasi pembuluh darah (Cao, Quan, & Zhuang, 2019). Temuan penelitian mengungkapkan bahwa latihan dengan intensitas tinggi terhadap pasisen yang sedang mejalani kemoterapi dapat meningkatkan kesehatan (Mijwel et al, 2019), terhadap kapasitas aerobic kepada penderita diabet tipe 2 (Hwang et al, 2019) Terdapat pengaruh yang sama antara HIIT dan intensitas moderat terhadap perubahan kualitas hidup dengan indikator massa otot dan penurunan lemak tubuh (Mugele et al, 2019). Latihan dengan intensitas tinggi ternyata hasilnya sama dengan intensitas moderat kontinus terhadap pengukuran antopometri tubuh (Andreato, Esteves, Coimbra, Moraes, & de Carvalho, 2019).…”
Section: Pendahuluanunclassified